TEKNIK PERMAINAN IMPROVISASI KEYBOARD PADA LAGU KIDUNG JEMAAT NO. 375 â€œSAYA MAU IKUT YESUSâ€ DI GEREJA HKI HUTAGURGUR - Simatupang, Jaka Pranata (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The purpose of this research is to add insight into the playing of keyboard instruments and what techniques can be used in playing the keyboard one of them improvised music playing techniques by playing music in whorship in the Church. The benefits of the research to explain the technique of improvised keyboard music playing in the accompaniment of processional worship at the HKI Curch Hutagurgur. Applied to this improvisation technique using the song of the Curch numbre 375 â€œI Want To Follow Jesusâ€ during the procession worship at the HKI Curch Hutagurgur. The study uses qualitative research that makes direct observations and gets information from several related source.Â The author lifts the song â€œI Want To Follow Jesusâ€and apply it through a keyboard instrument using an improvised playing music to add some melodies that are not in the original song sheet so that the atmosphere of entering the Church is more enjoying the music. The method used for this improvised music playing yechnique through melodi scale and chord transfer called chord bridges to go to the next chord on the song I Want To Follow Jesus. In improvised playing dont have to match the writen scores, because improvisation is a spontaneous idea that is created directly unconciously and without planed.The information contained in this thesis is the method using and appliying improvised playing techniques through stages wich is explained in playing music especially in the field of instruments keyboard in the use of improvisation first know the song that will be played to in the playing of improvisation more broadly in playing the melodies wich increase through the idea appear alone on the chord song moves. Perferably inside the Church player is sick of having to practice more in music playing techniques espesially on keyboard instruments because in aChurch instrument the most importaint keyboard in accompanying Church worship.